Pembawa Pesan Terdepan: Diaspora Dalam Gastrodiplomasi Indonesia - Trihartono, Agus; Purwowibowo, Purwowibowo; Santoso, Budi; Hara, Abubakar Eby (Laboratorium Sosiologi FISIP Universitas Jember, 2020)
This paper discusses the role of diaspora in Indonesian gastro-diplomacy. As a new country in culinary diplomacy, the role of the Indonesian diaspora is not dominant but not unimportant. The diaspora directly or not has popularized Indonesian food in foreign countries. Some of them have successfully managed Indonesian restaurants, although there are also some who are less successful. Learning from the experiences of countries already established in this culinary diplomacy such as India, China, Turkey and Vietnam, Indonesia needs to popularize more Indonesian food in many activities such as food festivals. In addition to this, the diaspora can increase the presence and visibility of Indonesian food through narratives in various printed and social media. Books and information on Indonesian cuisine, for example, are still very limited both in printed and digital media. In the current era, what is known as culinary fictions is one of the important aspects that can support gastro diplomacy.Keywords: Gastrodiplomacy, Diaspora, Indonesia Makalah ini membahas peran diaspora dalam gastro diplomasi Indonesia. Sebagai negara baru dalam diplomasi kuliner, peran diaspora Indonesia tidak dominan tetapi cukup penting. Diaspora secara langsung atau tidak telah mempopulerkan makanan Indonesia di luar negeri. Beberapa dari mereka telah berhasil mengelola restoran Indonesia, walaupun ada juga yang kurang berhasil. Belajar dari pengalaman negara-negara yang telah mapan dalam diplomasi kuliner ini seperti India, Cina, Turki dan Vietnam, Indonesia perlu mempopulerkan lebih banyak makanan Indonesia dalam banyak kegiatan seperti festival makanan. Selain itu, diaspora dapat meningkatkan kehadiran dan visibilitas makanan Indonesia melalui narasi di berbagai media cetak dan sosial. Buku dan informasi tentang masakan Indonesia, misalnya, masih sangat terbatas baik di media cetak maupun digital. Di era saat ini, apa yang dikenal sebagai fiksi kuliner adalah salah satu aspek penting yang dapat mendukung gastro diplomasi.Kata kunci: Gastrodiplomasi, Diaspora, Indonesia